Impact behaviors of poly-lactic acid based biocomposite reinforced with unidirectional high-strength magnesium alloy wires - Xuan Li (Progress in Natural Science: Materials International, 2014)
A novel poly-lactic acid (PLA) based biocomposite reinforced with unidirectional high-strength magnesium alloy (Mg-alloy) wires for bone fracture fixation was fabricated by hot-compressing process. The macroscopical and microscopical impact behaviors of the biocomposite were investigated using impact experiments and finite element method (FEM), respectively. The results indicated that the biocomposite had favorable impact properties due to the plastic deformation behavior of Mg-alloy wires during impact process. While the content of Mg-alloy wires reached 20 vol%, the impact strength of the composite could achieve 93.4 kJ/m2, which is approximate 16 times larger than that of pure PLA fabricated by the same process. According to FEM simulation results, the complete destruction life of the composites during impact process increased with increasing volume fraction of Mg-alloy wires, indicating a high impact-bearing ability of the composite for bone fracture fixation. Simultaneously, the energy absorbed by Mg-alloy wires in the composites had a corresponding increase. In addition, it denoted that the impact properties of the composites are sensitive to the initial properties of the matrix material.